Development of Entrepreneurship-Based Mathematical E-Module and Its' Learning with PBL to Improve Students' Mathematical Problem Solving Ability (Unnes Journal of Mathematics Education, 2023)
The purpose of this study was to determine the validity of the entrepreneurship-based mathematics E-Module, the practicality and effectiveness of learning mathematics with the PBL model assisted by the entrepreneurship-based mathematics E-Module to improve students' mathematical problem solving abilities. This research is a development research with the ADDIE model which is applied to class XI of SMK Negeri 1 Lemahabang, Cirebon Regency. The results showed that the entrepreneurship-based mathematics E-Module was declared valid with a percentage of the E-Module value of 92.88% in the "Very Eligible" category. Mathematics learning with the PBL model assisted by the E-Module mathematics based on entrepreneurship is stated to be (1) practical with a percentage of 86.9% of students and 96% of teachers falling into the "Very Practical" category; (2) effective based on the results of the posttest which showed that the experimental class achieved individual learning mastery of 75% with and achieved 75% classical learning completeness compared to the control class which did not achieve individual and classical learning mastery with grades . In addition, through the independent sample t test, it was found that the posttest results of the experimental class were better than the control class.